Thyroglobulin measurement in the needle washout for diagnosis of lymph node metastases of differentiated thyroid cancer - N. V. Severskaya; I. V. Chebotareva; N. V. Zhelonkina; M. I. Ryzhenkova; A. A. Ilyin; P. A. Isaev; V. V. Polkin; S. A. Ivanov; A. D. Kaprin (Опухоли головы и шеи)
Introduction. Measurement of thyroglobulin (Tg) in a washout after fine-needle aspiration (FNA) is recommended for the diagnosis of metastases of differentiated thyroid cancer (DTC), but the method is not standardized and there is no recommended threshold value of Tg washout, which makes it difficult to interpret the results.Aim. To analyze Tg in the washout after FNA of lesions of different origin on the neck and to determine its optimal cutoff for the diagnosis of DTC metastases.Materials and methods. Ultrasound-guided FNA was performed in 1258 neck masses from 591 patients, 566 of them with confirmed DTC. In 1023 lesions, FNA was performed after thyroidectomy, 22 – after lobectomy, 213 – with preserved thyroid gland. The needle after FNA was washed in 1 ml of saline, in which the concentration of Tg was then examined. The level of Tg in the washout was compared with the histological (n = 522) or cytological diagnosis if no surgery was performed. The cut-off for Tg washout was determined by ROC analysis.Results. DTC lymph node metastases detected in 577 specimens. Nine specimens were obtained from metastases of thyroid cancer (TC) that does not express Tg (anaplastic TC, poorly differentiated TC, columnar-cell variant DTC), 22 – from neck metastases of other malignancy (lung cancer, mucinous soft tissues tumor, ovarian cancer, esophageal cancer, melanoma, neuroendocrine tumor), 6 – from other tumors of the neck (lymphoma, parathyroid adenoma, neurinoma). In 26 cases, the specimen was regarded as normal thyroid tissue left after thyroidectomy, 37 – postoperative seroma or granuloma, 1 – cyst of the neck, 578 – lymph node hyperplasia, 2 – sarcoidosis. The level of Tg washout from DTC metastasis and thyroid remnant significantly differed from that of non-thyroidal origin (p <0.0001). At the cut-off of 7.8 ng/ml, the sensitivity and specificity of Tg washout in the diagnosis of DTC metastases is 94 and 95 %, and at the cut-off of 20 ng/ml, 90 and 98 %, respectively. False-negative results were obtained from DTC with squamous metaplasia or sparse tumor cells in a specimen. False-positive results were obtained more often from lesions of level VI and IV compared with other localizations (8 % versus 4 %; p = 0.04). There were no differences in false positive rate in patients before and after thyroidectomy (p = 0.17), but in patients after thyroidectomy with a serum Tg >200 ng/ml, the false positive rate of Tg washout was significantly higher than that with a lower level of serum Tg (28 % versus 3 %; p = 0.0004). When comparing diagnostic performance of cytology and Tg washout, the advantage of the latter is in the diagnosis of cystic metastases, and the former is in the diagnosis of micrometastases and tumors that do not express Tg. Thyroglobulin in the washout increased the sensitivity of the cytology by 8 %. The combined use of these methods detected DTC metastases in 100 % of patients.Conclusion. Measurement of Tg in the washout is a useful addition to the cytology, increasing the diagnostic performance of the latter, mainly due to better detection of cystic metastases of DTC. The optimal suggested cut-off for Tg washout is 20 ng/mL, at which there are fewer false positives.